International Handbook of Love Transcultural and Transdisciplinary Perspectives - Mayer, Claude-Hélène; Vanderheiden, Elisabeth (Springer Nature Switzerland : Imprint: Springer, 2025)
Approx. 2500 p. 20 illus., 10 illus. in color.